Powdery mildews on lilac in western North America include Phyllactinia syringae, sp. nov. (4th May 2017) - Larsen, Harold J.; Braun, Uwe; Blomquist, Cheryl; Woods, Patrick; Mohan, S. Krishna
ABSTRACT: Two powdery mildews, Erysiphe syringae and the previously undescribed Phyllactinia syringae, sp. nov., occur on lilac in western North America. Phyllactinia syringae is found on common lilac, whereas E. syringae is found on Chinese lilac and, occasionally, common lilac. Infection by P. syringae is extremely unobtrusive until formation of a hypophyllous mycelial mat with chasmothecia in late fall. Infection by E. syringae in late summer is conspicuous, with its thick, superficial mycelial mat on the leaf upper surface detracting from the aesthetic appearance of the bush.